2020
DOI: 10.1177/0020731420979808
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Margins in Health Services Research: How Does Race Intersect With Gender and Socioeconomic Status to Shape Difficulty Accessing HealthCare Among Unequal Brazilian States?

Abstract: Research on healthcare inequities has centralized whether marginalized racial, gender, or socioeconomic (SES) groups are afforded equitable access to care, yet scant investigations have focused on how race intersects with other social statuses to shape difficulty accessing health services. Contextual specificity has also been under-researched in this field of knowledge. Data from 59,249 respondents 18 years of age and over from the 2013 Brazilian National Health Survey were analyzed using multilevel regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
1
7
0
1
Order By: Relevance
“…The higher coverage by the FHS among Blacks has not been followed by lower perceived difficulty accessing health services, though, which also confirms our H1. Mirroring previous research findings [HM Constante and JL Bastos 17 , who further adjusted the analysis for a range of covariates, such as level of education and gender], our results consistently show that perceived difficulty accessing health services was higher among Blacks than whites across the entire period of observation and in all Brazilian geographic regions. This subjective indicator of healthcare access may not be grounded on lived experiences within the health system, but can certainly affect healthcare seeking behaviors and the overall satisfaction with care, which will then influence future experiences with service provision.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The higher coverage by the FHS among Blacks has not been followed by lower perceived difficulty accessing health services, though, which also confirms our H1. Mirroring previous research findings [HM Constante and JL Bastos 17 , who further adjusted the analysis for a range of covariates, such as level of education and gender], our results consistently show that perceived difficulty accessing health services was higher among Blacks than whites across the entire period of observation and in all Brazilian geographic regions. This subjective indicator of healthcare access may not be grounded on lived experiences within the health system, but can certainly affect healthcare seeking behaviors and the overall satisfaction with care, which will then influence future experiences with service provision.…”
Section: Discussionsupporting
confidence: 72%
“…Building on a recent publication 17 that documented racial inequities in difficulty accessing health services in Brazil, the present study analyses racial inequities in healthcare over a period of ten years. The study aimed to estimate racial inequities in access to health services in three different policy scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have contributed to socioeconomic disadvantage and worse health outcomes, including high infant and maternal mortality, low life expectancy, poor health, and social infrastructure [ 36 ]. Further, the COVID-19 pandemic has been shown to disproportionately impact racial minorities in other countries, and health care inequalities for black and pardo groups in Brazil have been shown typically parallel those of racial and ethnic minorities in the United States, China, and the United Kingdom [ 37 ]. For instance, a study of 101 black Americans living with HIV in California showed that those who had more negative impacts from COVID-19 demonstrated lower ART adherence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, recent studies have demonstrated the benefits of instruments that consider shared experiences at the intersections of race, gender, sexual orientation, and other axes of inequality. 13 , 14 However, no previous investigation has focused on MSM and TGNB, examining the varying salience of specific forms of discrimination, such as racism.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Ultimately, racism jeopardizes the possibility of several opportunities, including access to health care, which directly contributes to worse health outcomes for Black compared to White Brazilians. 14 , 19 …”
Section: Introductionmentioning
confidence: 99%